UPAYA PENINGKATAN LITERASI EKONOMI BAGI SISWA SD DALAM MENYONGSONG ERA SOCIETY 5.0 - Maritim, Ery; Damayanti, Maya; Susilowati, Diah; Budiarso, Aji (Dharmas Education Journal (DE_Journal), 2024)
The rapid development of technology and science today has had a complex impact on human life, including in the field of education. The demand for quality human resources who have a good work ethic is increasing. Therefore, education has an important role in improving the quality of human life. This research aims to increase the economic literacy of elementary school (SD) students in facing the era of Society 5.0 where there is greater emphasis that technology and its functions have become part of human life. Method Used: This research uses a literature review study method. This method is systematic, explicit, and reproducible for identifying, evaluating, and synthesizing papers from previous research. The research was carried out through several stages by practitioners and experts, by combining references from research and conceptual articles in reputable national journals taken via Google Scholar and others. Research Results: The research results show that learning economics at the elementary school level can increase students' economic literacy. Teachers can use a variety of teaching efforts tailored to students' abilities to provide an understanding of basic economic concepts. Economic literacy helps students understand daily economic activities and make more rational decisions. Providing an understanding of economic literacy also requires intervention from families and schools.